2021
DOI: 10.3389/fimmu.2021.663303
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Induce the Epithelial-Mesenchymal Transition: Implications in Post-COVID-19 Fibrosis

Abstract: The release of neutrophil extracellular traps (NETs), a process termed NETosis, avoids pathogen spread but may cause tissue injury. NETs have been found in severe COVID-19 patients, but their role in disease development is still unknown. The aim of this study is to assess the capacity of NETs to drive epithelial-mesenchymal transition (EMT) of lung epithelial cells and to analyze the involvement of NETs in COVID-19. Bronchoalveolar lavage fluid of severe COVID-19 patients showed high concentration of NETs that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 37 publications
(48 reference statements)
1
46
0
2
Order By: Relevance
“…In this study we show that the network of upregulated proteins is common across multiple cancer sub-types and largely distinguishes epithelial and mesenchymal forms of the disease (Figure 8). Moreover, such states are common to diabetes, neurodegenerative disorders, and infection driven syndromes – including severe COVID-19 (Lambert and Weinberg, 2021; Nieto et al, 2016; Pandolfi et al, 2021). This raises the possibility that cell shape changes which results in MTNO, and/or alter Kinesin-1 activity drive a common state which leads to different disease based on the cell of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we show that the network of upregulated proteins is common across multiple cancer sub-types and largely distinguishes epithelial and mesenchymal forms of the disease (Figure 8). Moreover, such states are common to diabetes, neurodegenerative disorders, and infection driven syndromes – including severe COVID-19 (Lambert and Weinberg, 2021; Nieto et al, 2016; Pandolfi et al, 2021). This raises the possibility that cell shape changes which results in MTNO, and/or alter Kinesin-1 activity drive a common state which leads to different disease based on the cell of origin.…”
Section: Discussionmentioning
confidence: 99%
“…During differentiation from epithelial to mesenchymal forms, cells change from apicobasally polarized epithelial cuboidal cells with cell-cell adhesions such as adherens and tight junctions, to protrusive mesenchymal, fibroblast-type cells with leading edge polarity and the formation of extensive cell-ECM (Extracellular Matrix) adhesions. Dysregulation of EMP has been implicated in cancers, fibrotic diseases, aging related pathologies, and correlates with the severity of infection-driven sequelae such as those following COVID-19 infection (Lambert and Weinberg, 2021; Nieto et al, 2016; Pandolfi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other study identified a variant on 3p21.31 region associated with increased respiratory failure risk in COVID-19 that enhances expression of leucine zipper transcription factor like 1 gene ( LZTFL1 ). LZTFL1 regulates a viral response pathway and is associated with epithelial-mesenchymal transition and it is possible that this epithelial dysfunction is driven by neutrophil extracellular traps ( 112 , 113 ).…”
Section: Nets Drive Thrombosis In Covid-19mentioning
confidence: 99%
“…A different study using post-mortem samples revealed increased levels of neutrophil extracellular traps (NET), which induce EMT in neighboring cells [73]. The increased presence of NETs positively correlates with the severity of COVID-19 and the elevated expression of EMT markers [74]. Importantly, a recent study showed that sera obtained from COVID-19 patients induce EMT in cancer cells, although the specific mechanism and whether SARS-CoV-2 makes patients more vulnerable to more aggressive forms of cancer remain to be determined [75].…”
Section: Cell Plasticity and Viral Infection: A Key Role For Emt In Virus-induced Cell Reprogrammingmentioning
confidence: 99%